Improved home BP profile with dapagliflozin is associated with amelioration of albuminuria in Japanese patients with diabetic nephropathy: the Yokohama add-on inhibitory efficacy of dapagliflozin on albuminuria in Japanese patients with type 2 diabetes study (Y-AIDA study) - Kinguchi, Sho (Cardiovasc Diabetol, 2019)
BACKGROUND: The Y-AIDA study was designed to investigate the renal- and home blood pressure (BP)-modulating effects of add-on dapagliflozin treatment in Japanese individuals with type 2 diabetes mellitus (T2DM) and albuminuria. METHODS: We conducted a prospective, multicenter, single-arm study. Eighty-six patients with T2DM, HbA1c 7.0–10.0%, estimated glomerular filtration rate (eGFR) ≥ 45 mL/min/1.73 m(2), and urine albumin-to-creatinine ratio (UACR) ≥ 30 mg/g creatinine (gCr) were enrolled, and 85 of these patients were administered add-on dapagliflozin for 24 weeks. The primary and key secondary endpoints were change from baseline in the natural logarithm of UACR over 24 weeks and change in home BP profile at week 24. RESULTS: Baseline median UACR was 181.5 mg/gCr (interquartile range 47.85, 638.0). Baseline morning, evening, and nocturnal home systolic/diastolic BP was 137.6/82.7 mmHg, 136.1/79.3 mmHg, and 125.4/74.1 mmHg, respectively. After 24 weeks, the logarithm of UACR decreased by 0.37 ± 0.73 (P < 0.001). In addition, changes in morning, evening, and nocturnal home BP from baseline were as follows: morning systolic/diastolic BP − 8.32 ± 11.42/− 4.18 ± 5.91 mmHg (both P < 0.001), evening systolic/diastolic BP − 9.57 ± 12.08/− 4.48 ± 6.45 mmHg (both P < 0.001), and nocturnal systolic/diastolic BP − 2.38 ± 7.82/− 1.17 ± 5.39 mmHg (P = 0.0079 for systolic BP, P = 0.0415 for diastolic BP). Furthermore, the reduction in UACR after 24 weeks significantly correlated with an improvement in home BP profile, but not with changes in other variables, including office BP. Multivariate linear regression analysis also revealed that the change in morning home systolic BP was a significant contributor to the change in log-UACR. CONCLUSIONS: In Japanese patients with T2DM and diabetic nephropathy, dapagliflozin significantly improved albuminuria levels and the home BP profile. Improved morning home systolic BP was associated with albuminuria reduction. Trial registration The study is registered at the UMIN Clinical Trials Registry (UMIN000018930; http://www.umin.ac.jp/ctr/index-j.htm). The study was conducted from July 1, 2015 to August 1, 2018. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12933-019-0912-3) contains supplementary material, which is available to authorized users.